Synthesis of neutral and cationic tripyridylporphyrin-D-galactose conjugates and the photoinactivation of HSV-1 - Tome, Joao P. C. (2015)
Neutral and cationic tripyridylporphyrin-D-galactose conjugates were synthesized and their antiviral activity against herpes simplex virus type 1 (HSV-1) was evaluated. At non-cytotoxic concentrations the studied compounds show significant antiviral activity after photoactivation. The influence of photoactivation on drug treated cells was also analyzed, at different times of infection with HSV-1, for a neutral (1b) and a cationic glycoporphyrin (3b) derivative. The results show that the inhibition of the viral yield is more dependent on photoactivation for compound 1b than for compound 3b. These two compounds also differ in the inhibitory effect during the viral replicative cycle: while compound 3b inhibits the viral yield at all the addition times assayed, compound 1b is more efficient in later times of infection. (c) 2007 Elsevier Ltd. All rights reserved.